2018
DOI: 10.1021/acsami.8b11596
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Robust Ultraviolet Photodetector Array Based on Self-Assembled Graphene/C60 Hybrid Films

Abstract: Graphene has been widely investigated for use in high-performance photodetectors due to its broad absorption band and high carrier mobility. While exhibiting remarkably strong absorption in the ultraviolet range, the fabrication of a large-scale integrable, graphene-based ultraviolet photodetector with long-term stability has proven to be a challenge. Here, using graphene as a template for C assembly, we synthesized a large-scale all-carbon hybrid film with inherently strong and tunable UV aborption. Efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…[95][96][97] Such novel materials also need to combine with other materials to promote entire performance. 39,73,98,99 Qiao et al incorporated a similar hexagonal symmetry Bi 2 Te 3 with graphene as shown in Figure 5G, the photodetector demonstrated a strong and broadband responsivity reach telecommunication band (35 A/W and extend to 1550 nm depicted in Figure 5H). 73…”
Section: Single Layer Enhanced Photoconductorsmentioning
confidence: 99%
“…[95][96][97] Such novel materials also need to combine with other materials to promote entire performance. 39,73,98,99 Qiao et al incorporated a similar hexagonal symmetry Bi 2 Te 3 with graphene as shown in Figure 5G, the photodetector demonstrated a strong and broadband responsivity reach telecommunication band (35 A/W and extend to 1550 nm depicted in Figure 5H). 73…”
Section: Single Layer Enhanced Photoconductorsmentioning
confidence: 99%
“…The device can directly convert optical stimuli into electrical pulses in a highly neuron-like fashion and exhibits flexible tuning of both the short-and long-term plasticity, as shown in Figure 6(g). Now all-carbon hybrid based on graphene/C 60 has attracted increasing attention because of their longterm stability, facile processing and large-scale processability [161][162][163][164] act as a potential candidate for future integrable optoelectronic applications. Wang group [161] demonstrated a large-scale integrable ultraviolet arrayed photodetector employing large-area graphene/C 60 hybrids, as shown in Figure 6(h) and (i).…”
Section: All-carbon Hybrids For Optoelectronicsmentioning
confidence: 99%
“…Now all-carbon hybrid based on graphene/C 60 has attracted increasing attention because of their longterm stability, facile processing and large-scale processability [161][162][163][164] act as a potential candidate for future integrable optoelectronic applications. Wang group [161] demonstrated a large-scale integrable ultraviolet arrayed photodetector employing large-area graphene/C 60 hybrids, as shown in Figure 6(h) and (i). Remarkably, the efficient exciton dissociation at the interface enables high photoconductive gain and a photoresponsivity exceeding 10 7 AW −1 for 200 nm irradiation.…”
Section: All-carbon Hybrids For Optoelectronicsmentioning
confidence: 99%
“…Organic π‐conjugated small molecule‐ and polymer‐based optoelectronic devices are of extraordinary significance for their merits over their inorganic counterparts, including excellent mechanical flexibility, cost‐effective fabrication, and tunable optoelectronic properties by rational molecular structure design, and broad material choices . More importantly, organic semiconductors can efficiently absorb light in the optical spectrum from UV to NIR either panchromaticly or selectively and show good photogeneration yield, which enables their successful development in the field of light detection . Panchromatic sensitive materials have aroused considerable attention for light detectors in various fields such as environmental monitoring, optical communication, or laboratory instrumentation for optical spectroscopy .…”
Section: Introductionmentioning
confidence: 99%